The Effects of Streptozotocin-Induced Diabetes and Insulin Treatment on Carnitine Biosynthesis and Renal Excretion - Aman Upadhyay (MDPI AG, 2021)
Carnitine insufficiency is reported in type 1 diabetes mellitus. To determine whether this is accompanied by defects in biosynthesis and/or renal uptake, liver and kidney were obtained from male Sprague-Dawley rats with streptozotocin-induced diabetes. Diabetic rats exhibited the metabolic consequences of type 1 diabetes, including hypoinsulinemia, hyperglycemia, and increased urine output. Systemic hypocarnitinemia, expressed as free carnitine levels, was evident in the plasma, liver, and kidney of diabetic rats. Compared to control rats, the low free carnitine in the plasma of diabetic rats was accompanied by decreased expression of γ-butyrobetaine hydroxylase in liver and kidney, suggesting impaired carnitine biosynthesis. Expression of organic cation transporter-2 in kidney was also reduced, indicating impaired renal reabsorption, and confirmed by the presence of elevated levels of free carnitine in the urine of diabetic rats. Insulin treatment of diabetic rats reversed the plasma hypocarnitinemia, increased the free carnitine content in both kidney and liver, and prevented urinary losses of free carnitine. This was associated with increased expression of γ-butyrobetaine hydroxylase and organic cation transporter-2. The results of our study indicate that type 1 diabetes induced with streptozotocin disrupts carnitine biosynthesis and renal uptake mechanisms, leading to carnitine insufficiency. These aberrations in carnitine homeostasis are prevented with daily insulin treatment.